INVERSI AVO MENGGUNAKAN METODA MARQUARDT UNTUK IDENTIFIKASI POROSITAS RESERVOAR - Alam, Syamsu
Abstract : By utilizing the AVO inversion computation based on Shuey (1985) equation, which shows the relationship between the reflection coefficient (It) and the increament of the incidence angle (0), the poisson\'s values of two adjacent layers can be obtained. By considering that Shuey equation is an non-linear form, the inversion method used is the Marquardt non-linear optimation method. Basically this method is used by expanding function (f)) into a Taylor series, by neglecting the second and higher orders. This method is commonly called as generalized linear inversion (Keys, 1986). The poisson\'s values (a) obtained from the inversion can be used to identify fluid type content in the reservoir, gas or water, as the causes of the AVO anomaly. If the content of the reservoir is gas, then the problem is how big the existing reserve. One parameter for computing the reserve is the porosity. Therefore for computing the porosity, an empirical equation relating the Young modulus (E) and porosity (4) developed by Piggot (1990) is used. This equation is valid only for carbonate reservoir. The Young modulus value is obtained by computing the S-wave velocity (Vs), using the P-wave velocity (Vt), poisson\'s values resulted from the inversion and the density (p). The porosity computation using AVO inversion methode yield similar result with the computation using well data. This shown by computation result of CDP-222 which gives value of 36.6%, while from well CCH P1 located on the same CDP the value is 20 - 38%. Main advantages of this method is that it can be used to estimate the porosity distribution, either in vertical or lateral direction. The knowledge about the porosity distribution will in turn enhance the accuracy of reserve size computation.